Implementation of access controls for a professional practice management system - Torres Correa, Robert Emmanuel (2023)
This article presents a web information system that will facilitate the management of professional practices at the National University of Trujillo. For this, an agile SCRUM methodology was applied because it is adaptable to the constant changes in the software development process and the access controls provided by the ISO 27001:2013 standard with the aim of guaranteeing the integrity, authenticity and availability of data. the information assets that the system possesses. The results obtained support the implementation of two-factor authentication and digital signature as essential controls for information management according to the calculated reliability. It is concluded that the access controls provide security in the information handled in the system according to the trust tests.